Polychromatic Supplemental Lighting from underneath Canopy Is More Effective to Enhance Tomato Plant Development by Improving Leaf Photosynthesis and Stomatal Regulation - Song, Yu; Jiang, Chengyao; Gao, Lihong (Frontiers in Plant Science, 2016)
Light insufficient stress caused by canopy interception and mutual shading is a major factor limiting plant growth and development in intensive crop cultivation. Supplemental lighting can be used to give light to the lower canopy leaves and is considered to be an effective method to cope with low irradiation stress. Leaf photosynthesis, stomatal regulation and plant growth and development of young tomato plants were examined to estimate the effects of supplemental lighting with various composite spectra and different light orientations. Light-emitting diodes (LEDs) of polychromatic light quality, red + blue (R/B), white + red + blue (W/R/B), white + red + far-red (W/R/FR), and white + blue (W/B) were assembled from the underneath canopy or from the inner canopy as supplemental lighting resources. The results showed that the use of supplemental lighting significantly increased the photosynthetic efficiency, and reduced stomatal closure while promoting plant growth. Among all supplemental lighting treatments, the W/R/B and W/B from the underneath canopy had best performance. The different photosynthetic performances among the supplemental lighting treatments are resulted from variations in CO2 utilization. The enhanced blue light fraction in the W/R/B and W/B could better stimulate stomatal opening and promote photosynthetic electron transport activity, thus better improving photosynthetic rate. Compared with the inner canopy treatment, the supplemental lighting from the underneath canopy could better enhance the carbon dioxide assimilation efficiency and excessive energy dissipation, leading to an improved photosynthetic performance. Stomatal morphology was highly correlated to leaf photosynthesis and plant development, and should thus be an important determinant for the photosynthesis and the growth of greenhouse tomatoes.